2017
DOI: 10.1001/jamaophthalmol.2017.0988
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diabetic Macular Edema and Proliferative Diabetic Retinopathy With Cardiovascular Disease

Abstract: IMPORTANCE Previous studies on the relationship between diabetic retinopathy (DR) and cardiovascular disease (CVD) focused on the early stages of DR. Understanding whether patients with type 2 diabetes and severe stages of DR (diabetic macular edema [DME] and proliferative diabetic retinopathy [PDR]) have a higher risk of CVD will allow physicians to more effectively counsel patients.OBJECTIVE To examine the association of severe stages of DR (DME and PDR) with incident CVD in patients with type 2 diabetes.DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 38 publications
6
75
0
2
Order By: Relevance
“…A recent meta-analysis revealed that patients with DME or PDR were more likely to have incident cardiovascular disease (CVD) and fatal CVD when compared to those without DME or PDR in type 2 diabetes mellitus [44]. It is accepted that fluid retention due to cardiac failure, or another CVD can exacerbate DME and may be an important concern when managing it [45].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis revealed that patients with DME or PDR were more likely to have incident cardiovascular disease (CVD) and fatal CVD when compared to those without DME or PDR in type 2 diabetes mellitus [44]. It is accepted that fluid retention due to cardiac failure, or another CVD can exacerbate DME and may be an important concern when managing it [45].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the retinal arteriolar and venular caliber were associated with increased risk of stroke (3)(4)(5) and cardiovascular mortality in subjects without diabetes (6,7). Similarly, diabetic or other retinal vascular disease has been suggested to predict peripheral artery disease (PAD) and cardiovascular mortality in type 2 diabetes (8)(9)(10)(11). We have previously shown a relationship among diabetic retinopathy, stroke, and mortality in T1D (2,12).…”
mentioning
confidence: 90%
“…The presence of DME and proliferative retinopathy is associated with increased risk of fatal and incident cardiovascular disease events (10). Nonproliferative and proliferative retinopathy are also associated with peripheral arterial disease (65), suggesting that patients with DR and DME may need more vigilant surveillance for vascular disease.…”
Section: Association Of Diabetes-related Eye Disease With Vascular DImentioning
confidence: 99%
“…The ocular manifestations of diabetes develop in parallel with renal and neuropathic complications; they can present as manifestations of diabetes or of glucose intolerance (7), or they can develop in the late stages of the disease (8). The presence of DR, and particularly advanced DR, is associated with a greater risk of other systemic manifestations of diabetes, including stroke, heart attack, and renal insufficiency (9,10). Likewise, advancing renal disease, in particular, is likely to accelerate DR due to hypertension, anemia, and inflammation (11).…”
mentioning
confidence: 99%